The learning society - Husén, Torsten, 1916-2009 (A University paperback original, UP 533, 1974)
Welcome to the final season of the adventures of the USS Voyager- Season 7. Stranded in unknown and hostile space. This season's highlights include deadly renegade holographic Starfleet officers, errant Klingons who worship an unborn baby, the Doctor trapped in Seven of Nine's body, the return of Q, and Voyager's triumphal return to Earth ! While a desperate Borg Queen takes to murdering her own drones to halt the spread of individuality enjoyed by the occupiers of Unimatrix Zero, Captain Janeway's team will continue to be a thorn in her side, delivering not one, but two major blows to the Collective this year.